2021
DOI: 10.1155/2021/5876841
|View full text |Cite
|
Sign up to set email alerts
|

SIRT5‐Related Desuccinylation Modification Contributes to Quercetin‐Induced Protection against Heart Failure and High‐Glucose‐Prompted Cardiomyocytes Injured through Regulation of Mitochondrial Quality Surveillance

Abstract: Myocardial fibrosis represents the primary pathological change associated with diabetic cardiomyopathy and heart failure, and it leads to decreased myocardial compliance with impaired cardiac diastolic and systolic function. Quercetin, an active ingredient in various medicinal plants, exerts therapeutic effects against cardiovascular diseases. Here, we investigate whether SIRT5- and IDH2-related desuccinylation is involved in the underlying mechanism of myocardial fibrosis in heart failure while exploring rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 61 publications
0
50
0
Order By: Relevance
“…The mechanism may be to inhibit the activation of MAPK pathway through ROS [ 20 ]. Quercetin inhibited myocardial fibrosis and improved cardiac function by increasing mitochondrial energy metabolism and regulating mitochondrial fusion/fission and mitochondrial biosynthesis while inhibiting the inflammatory response and oxidative stress injury [ 21 ]. Kaempferol (KPF) protects cardiomyocytes from many aspects because of its significant inhibition of inflammatory response and oxidative stress [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism may be to inhibit the activation of MAPK pathway through ROS [ 20 ]. Quercetin inhibited myocardial fibrosis and improved cardiac function by increasing mitochondrial energy metabolism and regulating mitochondrial fusion/fission and mitochondrial biosynthesis while inhibiting the inflammatory response and oxidative stress injury [ 21 ]. Kaempferol (KPF) protects cardiomyocytes from many aspects because of its significant inhibition of inflammatory response and oxidative stress [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has a good therapeutic effect on cardiovascular diseases. Wang et al (144) have shown that a certain dose of quercetin can significantly improve myocardial ischemia injury and myocardial fibrosis after acute MI, improve cardiac function and ejection fraction, maintain cardiomyocyte activity, improve mitochondrial energy metabolism in cardiomyocytes, and reduce the incidence of heart failure. Further studies have shown that the therapeutic effect of quercetin may be related to SIRT5 mediated de-succinylation of IDH2 and upregulation of mitophagy (144).…”
Section: Pharmacological Intervention In Animalsmentioning
confidence: 99%
“…Wang et al (144) have shown that a certain dose of quercetin can significantly improve myocardial ischemia injury and myocardial fibrosis after acute MI, improve cardiac function and ejection fraction, maintain cardiomyocyte activity, improve mitochondrial energy metabolism in cardiomyocytes, and reduce the incidence of heart failure. Further studies have shown that the therapeutic effect of quercetin may be related to SIRT5 mediated de-succinylation of IDH2 and upregulation of mitophagy (144). However, SIRT5 knockdown eliminated the inhibitory effect of quercetin on the inflammatory response of NLRP3 in cardiomyocytes, and the activity of cardiomyocytes was further reduced.…”
Section: Pharmacological Intervention In Animalsmentioning
confidence: 99%
“…Chang et al showed that quercetin pretreatment protects human cardiomyocytes from hypoxia-induced oxidative-stress damage by inhibiting reactive-oxygen-species (ROS) production and oxidative-stress damage, improving mitophagy and energy metabolism, regulating mitochondrial/endoplasmic-reticulum function, and reducing apoptosis [ 52 ]. Furthermore, Cheng et al studied the effects of quercetin on mouse models of myocardial fibrosis and heart failure, finding that quercetin administration reduced myocardial fibrosis and enhanced cardiac function in high-glucose-exposed inflammation-injury cardiomyocyte cell line HL-1 [ 53 ]. These effects were partially mediated by increased mitochondrial energy metabolism as well as regulation of mitochondrial fusion/fission and mitochondrial biosynthesis.…”
Section: Flavonols and Their Cardioprotective Activitymentioning
confidence: 99%
“…These effects were partially mediated by increased mitochondrial energy metabolism as well as regulation of mitochondrial fusion/fission and mitochondrial biosynthesis. In addition, quercetin reduced the incidence of heart failure by inhibiting the inflammatory response and oxidative-stress injury, protecting mouse cardiomyocytes under inflammatory conditions, and improving myocardial fibrosis [ 53 ]. Similarly, in the ischemia/reperfusion-induced rat model, quercetin exerted cardioprotective effects by inhibiting inflammatory responses and improving contractility potential.…”
Section: Flavonols and Their Cardioprotective Activitymentioning
confidence: 99%